IMPROVING STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT TROUGH DRAW LABEL CAPTION (DLC) TECHNIQUE TO THE SECOND YEAR STUDENTS OF SMPN 1 PEUDADA (A Collaborative Classroom Action Research) - Misnawati Misnawati (FKIP, 2018)
The title of this research is: improving students’ ability in writing descriptive text through Draw Label Caption (DLC) technique to the second year students of SMPN 1 Peudada (A Collaborative Classroom Action Research). The researcher put two problems of this research with the question as follows: first, how does DLC technique improve the second year students’ writing ability in SMPN 1 Peudada? Second, how do the second year students of SMPN 1 Peudada respond toward the implementation of DLC technique in writing descriptive text? The purposes of this research were: first, to improve the second year students’ ability in writing descriptive text through DLC technique in SMPN 1 Peudada. Second, to know the responses of the second year students of SMPN 1 Peudada toward the implementation of DLC technique in writing descriptive text. This research was a collaborative classroom action research. The research subject was the second year students of SMPN 1 Peudada. The sample of this research was 25 students. The data was collected through the field note, writing test, students’ observation sheet, teacher’s observation sheet, and questionnaire. The data was analyzed through the descriptive qualitative research. After the researcher was done all the steps of action research (cycle I and cycle II) the students’ mean score increased from 70 in cycle I and became 77 in cycle II. Besides, from the observation sheet to the students’ activity, it was found that the percentage of the students’ participation during the teaching-learning process in writing class increases gradually. It was proved by the result of the observation sheet where taken at the beginning of cycle I, the percentage of the students’ participation was only 58,88% and it increased to 75,55% and became 85,5% in cycle II. And also, the list of questionnaire given to the students indicates that the student had positive responses toward the implementation of DLC technique in writing class. It was proved by overall mean score 3,31 that was categorized to the level of Agree. Key Words: Writing, DLC technique